Poređenje Friedvald, Martin/Hopkins i Sampson formula sa direktnim merenjem LDL kod hiperlipidemija i normolipidemijskih odraslih osoba: Poređenje Friedvald, Martin/Hopkins i Sampson formula sa direktnim merenjem LDL - ALPDEMİR, Medine and Alpdemir, Mehmet Fatih and Şeneş, Mehmet (Journal of Medical Biochemistry, 2024)
ABSTRACT Objective: In our study, we aimed to compare and validate the performance of the Friedewald, Martin/Hopkins, and Sampson formulae with direct LDL-C measurement. Material and Methods: The study was a retrospective investigation which by the Department of Medical Biochemistry of the Ankara Training and Research Hospital between 1 January 2021 and 31 December 2022. Our study evaluated the results of 6297 patients aged 18-99 years who underwent cholesterol panel TC, TG, HDL-C and direct LDL-C in our laboratory. Estimated LDL-C calculated according to Friedewald, Martin/Hopkins, and Sampson formulae. Results: All three formulae showed a stronger positive correlation with d-LDL-C (0.905, 0.897, and 0.886, respectively, for all data, p<0.001). In addition, when we compared the total median difference (1st-3rd quartile) of all formulae, it was it was -0.69 (-1.62-0.39) for Friedewald, 0.034 (-0.74 -1.14) for Martin/Hopkins and -0.40 (-1.19-0.55) for Sampson. According to Passing Bablok regression analyses, the intercept was determined as -0.97 (95% CI = -1.01 to -0.93), 0.41 (95%=0.37 to 0.44) and -0.05 (-0.08 to -0. 03) and slopes were calculated as 1.083 (95% CI = 1.07-1.09), 0.88 (0.88 to 0.89) and 0. 90 (95% = 0.89 to 0.90) for Friedewald, Martin/Hopkins and Sampson, respectively. Conclusions: Our findings suggest that Martin/Hopkins formula indicated a better performance than Friedewald and Sampson formulae. We figured out utilizing the Martin/Hopkins formula as a good alternative for estimated LDL-C in Turkish adults.